THE COOPERATIVE LEARNING CONCEPT ON QUR’AN - Zahra, Dwi Noviatul; Fasa, Muhammad Iqbal (Hunafa: Jurnal Studia Islamika, 2018)
Humans are social beings, that means beings who can not live without the help of others. Man as a creature of God, nothing is perfect and could not match his creator. No one man can live alone without the help of others, as rich as any property held. Based on this background, the researchers will present the concept definition ta’āwun? How ta’āwun concepts (cooperatif learning) in the Qur’an? Ta’āwun concept (cooperative learning) in the Koran that the researchers found were in al-Mā`idah verse 2, al-Naḥl verse 125, al-Anfāl verse 73, Al-‘Aṣr verses 1-3, and al-Taubah paragraph 71 which in these verses explain the urgency cooperate in goodness, in this case trying to connect with Islamic education. Ta’āwun (cooperative learning) when applied in the classroom will have some benefits, which can make students to be independent, creative, honing his abilities, cultivate social aspects, which in this case there are three aspects of the cognitive, affective and psychomotor.